Upaya Meningkatkan Kompetensi Strategis Matematis Melalui Pendekatan Metaphorical Thinking Siswa Kelas VIIA SMP Negeri 11 Yogyakarta - Sudarsono Sudarsono; Heni Nurrohmah (Jurnal Derivat, 2016)
The aims of this research is to improve students’ strategic mathematic ability. This research was conducted according to Class VII A Mathematic teacher’s explanation that students unable to find the mathematic relation from question and developing an effective solving method. It was supported by the Class VII A students’ mid test result, students found it difficult to solve a problem because 85% of 35 students unable to solve it. That means 30 students of Class VII A do not have the ability in strategic mathematic competence. This research is a Class Action Research (CAR) that conducted collaboratively. The subject of this research is Class VII students of SMP N 11 Yogyakarta that consists of 35 students. The object of this research is mathematics learning using Metaphorical Thinking approach to improve students’ mathematic strategic competence ability. This research consist of 2 cycles, there are 3 meetings for every cycle. Research data obtained from learning observation sheet, interview result, field note, written test and documentation. The result of this research show that students’ strategic mathematic competence is improving according to first and second cycle last test’s score. Average score pre-research which taken from mid semester test of Class VII A students is 66,22 with students’ KKM achievement percentage is 25,71%, while in the end of first cycle the average strategic mathematic competence ability test result improved into 74,14 with students’ KKM achievement percentage is 57,14%. Students’ strategic mathematic ability average score achieve the KKM on the second cycle with average score 84,74. The percentage of students’ which achieve KKM on second cycle is 77,14%.